Kronic hysteria: Exploring the intersection between Australian synthetic cannabis legislation, the media, and drug-related harm - Bright, Stephen; Bishop, Brian; Kane, Robert; Marsh, Alison; Barratt, Monica (Elsevier BV, 2013)
Background Having first appeared in Europe, synthetic cannabis emerged as a drug of concern in Australia during 2011. Kronic is the most well-known brand of synthetic cannabis in Australia and received significant media attention. Policy responses were reactive and piecemeal between state and federal governments. In this paper we explore the relationship between media reports, policy responses, and drug-related harm. Methods Google search engine applications were used to produce time–trend graphs detailing the volume of media stories being published online about synthetic cannabis and Kronic, and also the amount of traffic searching for these terms. A discursive analysis was then conducted on those media reports that were identified by Google as ‘key stories’. The timing of related media stories was also compared with self-reported awareness and month of first use, using previously unpublished data from a purposive sample of Australian synthetic cannabis users. Results Between April and June 2011, mentions of Kronic in the media increased. The number of media stories published online connected strongly with Google searches for the term Kronic. These stories were necessarily framed within dominant discourses that served to construct synthetic cannabis as pathogenic and created a ‘moral panic’. Australian state and federal governments reacted to this moral panic by banning individual synthetic cannabinoid agonists. Manufacturers subsequently released new synthetic blends that they claimed contained new unscheduled chemicals. Conclusion Policies implemented within in the context of ‘moral panic’, while well-intended, can result in increased awareness of the banned product and the use of new yet-to-be-scheduled drugs with unknown potential for harm. Consideration of regulatory models should be based on careful examination of the likely intended and unintended consequences. Such deliberation might be limited by the discursive landscape.